Requirement of Trichome Formation for the Growth-promoting Effects of Olivine for Enhanced Weathering in Arabidopsis thaliana - Minoru Ueda; Daisuke Todaka; Satoshi Takahashi; Junko Ishida; Maho Tanaka; Tokihiro Ikeda; Keiko Suzuki; Misako Miwa; Takeshi Uchiyama; Yasuhiro Ishimaru; Kazuhiro Sayama; Nobuyuki Uozumi; et al. (Journal of Plant Growth Regulation, 2026)
Enhanced rock weathering helps remove CO 2 from air and cools the Earth over geological time periods, while also promoting plant growth, but the molecular mechanism underlying enhanced plant growth is unclear. In this study, ionome and transcriptome analyses revealed the importance of trichome formation for the growth-promoting effects of olivine ground to enhance weathering. In Arabidopsis, the application of 10% (w/w) olivine improved plant growth (a 64.2% increase in leaf area) and caused a 24.7% increase in Mg accumulation determined by ICP-AES at 23 days after germination (DAG) under long-day (16 h light/8 h dark cycle) conditions. Elemental maps of olivine-treated plants at 10 DAG produced by micro-particle-induced x-ray emission showed that olivine significantly altered Mg, K, and S accumulation in trichomes on true leaves, suggesting that trichomes may be critical for olivine-induced growth. The growth of glabrous1 ( gl1-1 and gl1-4 ) mutants defective in trichome initiation was not promoted by olivine. A transcriptome analysis of shoots by RNA-seq from wild-type plants at 16 DAG indicated olivine suppressed biotic stress-responsive gene expression. Additionally, Zn homeostasis was disrupted by olivine in gl1 mutants, implying that decreased Zn availability may inhibit the positive effect of olivine on growth. Collectively, our data uncovered the importance of trichomes to the adaptation of plants to soils containing rock-powders for crop improvement and agricultural sustainability and suggest the possibility that applying olivine might modulate the growth–defense trade-off governed by ion homeostasis mediated through trichome development, leading to improved plant growth.

Modern silica sinter deposits from an island-arc setting and their potential for fossilizing plants - Aya Kubota; Ryo Taniguchi; Tomoyuki Ueda; Yasuhiro Iba (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Onnamides and a Novel Analogue, Onnamide G, as Potent Leishmanicidal Agents - Takahiro Jomori; Nanami Higa; Trianda Ayuning Tyas; Natsuki Matsuura; Yudai Ueda; Ayumi Suetake; Shin Miyazaki; Shuichi Watanabe; Sei Arizono; Yasuhiro Hayashi; Ko Yasumoto; Yuji Ise; et al. (Marine Biotechnology, 2025)
Leishmaniasis is a neglected tropical disease posing significant global health challenges. Given the limited effective treatment options and associated constraints, many patients are unable to complete therapy. In this study, we report the remarkable leishmanicidal activity of onnamides derived from the marine sponge Theonella sp. against the promastigote form of Leishmania major (IC 50 = 0.2–140 nM) and demonstrate their selectivity through cytotoxicity assessments on human hepatoma HepG2 cells. Structural-activity relationship (SAR) analyses were conducted using 6,7-dihydro-onnamide A and its analogs. Furthermore, we compared the action mechanisms of amphotericin B, the primary drug currently used for treatment, and the obtained onnamides. Based on biological evaluations and SAR studies, onnamides can be considered promising candidates for anti-leishmanial chemotherapy, warranting further investigation.

In-frame mutation in rice TEOSINTE BRANCHED1 (OsTB1) improves productivity under phosphorus deficiency - Takuma Ishizaki; Yoshiaki Ueda; Toshiyuki Takai; Kyonoshin Maruyama; Yasuhiro Tsujimoto (Plant Science, 2023)

Effect of a proton-pump inhibitor on intestinal microbiota in patients taking low-dose aspirin - Hiroyuki Tsujimoto; Yuki Hirata; Yasuhiro Ueda; Naohiko Kinoshita; Hideki Tawa; Yasuyoshi Tanaka; Ryoji Koshiba; Kazuhiro Ota; Yuichi Kojima; Kazuki Kakimoto; Toshihisa Takeuchi; Takako Miyazaki; et al. (European Journal of Clinical Pharmacology, 2021)

A novel challenge of nondestructive analysis on OGATA Koan’s sealed medicine by muonic X-ray analysis - Kayoko Shimada-Takaura; Kazuhiko Ninomiya; Akira Sato; Naomi Ueda; Motonobu Tampo; Soshi Takeshita; Izumi Umegaki; Yasuhiro Miyake; Kyoko Takahashi (Journal of Natural Medicines, 2021)

Railway embankment failure due to ballast layer breach caused by inundation flows - Ryota Tsubaki; Yoshihisa Kawahara; Yasuhiro Ueda (Natural Hazards, 2017)

Jasmonate signaling is activated in the very early stages of iron deficiency responses in rice roots - Takanori Kobayashi; Reiko Nakanishi Itai; Takeshi Senoura; Takaya Oikawa; Yasuhiro Ishimaru; Minoru Ueda; Hiromi Nakanishi; Naoko K. Nishizawa (Plant Molecular Biology, 2016)

Iron deficiency regulated OsOPT7 is essential for iron homeostasis in rice - Khurram Bashir; Yasuhiro Ishimaru; Reiko Nakanishi Itai; Takeshi Senoura; Michiko Takahashi; Gynheung An; Takaya Oikawa; Minoru Ueda; Aiko Sato; Nobuyuki Uozumi; Hiromi Nakanishi; Naoko K. Nishizawa (Plant Molecular Biology, 2015)

Genomic and serological detection of bat coronavirus from bats in the Philippines - Shumpei Tsuda; Shumpei Watanabe; Joseph S. Masangkay; Tetsuya Mizutani; Phillip Alviola; Naoya Ueda; Koichiro Iha; Satoshi Taniguchi; Hikaru Fujii; Kentaro Kato; Taisuke Horimoto; Shigeru Kyuwa; et al. (Archives of Virology, 2012)

Detection of bat coronaviruses from Miniopterus fuliginosus in Japan - Kazuya Shirato; Ken Maeda; Shumpei Tsuda; Kazuo Suzuki; Shumpei Watanabe; Hiroshi Shimoda; Naoya Ueda; Koichiro Iha; Satoshi Taniguchi; Shigeru Kyuwa; Daiji Endoh; Shutoku Matsuyama; et al. (Virus Genes, 2012)

Detection of a new bat gammaherpesvirus in the Philippines - Shumpei Watanabe; Naoya Ueda; Koichiro Iha; Joseph S. Masangkay; Hikaru Fujii; Phillip Alviola; Tetsuya Mizutani; Ken Maeda; Daisuke Yamane; Azab Walid; Kentaro Kato; Shigeru Kyuwa; et al. (Virus Genes, 2009)

Carbon-source-dependent transcriptional control involved in the initiation of cellular differentiation in Streptomyces griseus - Kenji Ueda; Kouki Endo; Hideaki Takano; Madoka Nishimoto; Yasumasa Kido; Yasuhiro Tomaru; Kouichi Matsuda; Teruhiko Beppu (Antonie van Leeuwenhoek, 2000)

Construction of Canine Herpesvirus Vector Expressing Foreign Genes Using a lacZ-TK Gene Cassette as a Double Selectional Marker - Xuenan Xuan; Yoshifumi Nishikawa; Yasuhiro Takashima; Kotaro Tuchiya; Susumu Ueda; Naoaki Yokoyama; Ken Maeda; Takeshi Mikami; Haruki Otsuka (Virus Genes, 1998)